2003
DOI: 10.1111/j.1471-0528.2003.02162.x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular endotheliosis in normal pregnancy and pre‐eclampsia

Abstract: Objective To investigate the proportion of women with findings characteristic for pre‐eclampsia, as opposed to renal disease, in a controlled study of hypertensive pregnant women undergoing antepartum renal biopsy. Design An observational prospective controlled study. Setting University Hospital of Lund, Sweden. Sample Thirty‐six previously healthy women with hypertensive disease in pregnancy, consecutively admitted to the antenatal ward at onset of disease during a 20 month period and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(66 citation statements)
references
References 22 publications
3
61
0
2
Order By: Relevance
“…VEGF, vascular endothelial growth factor. previous report (16). A dysregulation of, and the resulting imbalance between, proangiogenic and antiangiogenic factors is believed to cause endotheliosis.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…VEGF, vascular endothelial growth factor. previous report (16). A dysregulation of, and the resulting imbalance between, proangiogenic and antiangiogenic factors is believed to cause endotheliosis.…”
Section: Discussionmentioning
confidence: 81%
“…At least 50 glomeruli per section were examined, and the following parameters were scored: presence of endotheliosis, double contours of the glomerular basement membrane (tram tracking), swelling of podocytes (prominent presence of podocytes), mesangial changes, glomerulitis, and FSGS. As previously described by Strevens et al (16), endotheliosis was scored semiquantitatively as follows: 0 (no endotheliosis), 1 (,20% of the lumen was obliterated), 2 (20%-80% of the lumen was obliterated), or 3 (.80% of the lumen was obliterated). Global sclerosis was recorded as a percentage of the total number of glomeruli scored.…”
Section: Quantification Of Histologymentioning
confidence: 99%
“…These findings were further confirmed in a later study after augmentation of the GFR and RPF with an amino acid infusion (37). There are also very limited uncontrolled data from autopsy cases (38) and, more recently, controversial data from 12 thirdtrimester biopsies (39) to suggest that glomerular diameter may be greater than that measured in nonpregnant participants. Lastly, in the postpartum period, we utilized physiologic techniques to measure GFR, RPF, and oncotic pressure and computed a value for the two-kidney K f in 22 women 2 weeks after delivery and demonstrated that RPF returned to baseline values and oncotic pressure increased above control values.…”
Section: Renal Functionmentioning
confidence: 77%
“…Strevens et al 19 obtained renal biopsy samples in women with normal pregnancy, GH and PE; glomerular endotheliosis, which has been believed as a characteristic lesion found in women with PE, was present in all women with GH and PE, and almost half of the controls, although the degree of endotheliosis is more severe in women with PE than in women with GH, and in women with GH than in women with normal pregnancy, supporting our opinion that GH is a type of subclinical PE.…”
Section: Discussionmentioning
confidence: 99%